ARDUINO BASED DC MOTOR SPEED CONTROL - Saini, Hirdesh Kr.; Firoz, Shahid; Pandey, .Ashutosh (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
The Uno is a microcontroller board based on the ATmega328P. It has 14 digital input/output pins (of which 6 can be used as PWM outputs), 6 analog inputs, a 16 MHz quartz crystal, a USB connection, a power jack, an ICSP header and a reset button. It contains everything needed to support the microcontroller; simply connect it to a computer with a USB cable or power it with a AC-to-DC adapter or battery to get started.. You can tinker with your UNO without worrying too much about doing something wrong, worst case scenario you can replace the chip for a few dollars and start over again. "Uno" means one in Italian and was chosen to mark the release of Arduino Software (IDE) 1.0. This is called a boot loader. The ATmega328 on the Uno comes preprogrammed with a boot loader that allows you to upload new code to it without the use of an external hardwar programmer. It communicates using the original STK500 protocol we can also bypass the boot loader and program the microcontroller through the ICSP (In- Circuit Serial Programming) header using Arduino ISP B. 8 channel